Choline chloride/ urea as mild media for the synthesis of the chromonyl amidodiester fragments and succinimide derivatives - Jamaati, Hoda; Balalaie, Saeed; Rominger, Frank (ChemistrySelect, 2019)
A simple, green protocol has been accomplished for the synthesis of amidoesters 5 a-k in choline chloride/urea (1:2) through multicomponent reaction of 3-formyl chromone, Meldrum's acid, isocyanides and primary alcohols via a domino reaction. Carrying out the reaction using trifluoroethanol led to succinimide derivatives 6 a-d. Easy work-up, selectivity, and good to excellent yields are the advantages of this protocol.
Gesehen am 03.12.2019